A modified action framework to develop and evaluate academic-policy engagement interventions - Petra Mäkelä; Annette Boaz; Kathryn Oliver (Implementation Science, 2024)
Abstract Background There has been a proliferation of frameworks with a common goal of bridging the gap between evidence, policy, and practice, but few aim to specifically guide evaluations of academic-policy engagement. We present the modification of an action framework for the purpose of selecting, developing and evaluating interventions for academic-policy engagement. Methods We build on the conceptual work of an existing framework known as SPIRIT (Supporting Policy In Health with Research: an Intervention Trial), developed for the evaluation of strategies intended to increase the use of research in health policy. Our aim was to modify SPIRIT, (i) to be applicable beyond health policy contexts, for example encompassing social, environmental, and economic policy impacts and (ii) to address broader dynamics of academic-policy engagement. We used an iterative approach through literature reviews and consultation with multiple stakeholders from Higher Education Institutions (HEIs) and policy professionals working at different levels of government and across geographical contexts in England, alongside our evaluation activities in the Capabilities in Academic Policy Engagement (CAPE) programme. Results Our modifications expand upon Redman et al.’s original framework, for example adding a domain of ‘Impacts and Sustainability’ to capture continued activities required in the achievement of desirable outcomes. The modified framework fulfils the criteria for a useful action framework, having a clear purpose, being informed by existing understandings, being capable of guiding targeted interventions, and providing a structure to build further knowledge. Conclusion The modified SPIRIT framework is designed to be meaningful and accessible for people working across varied contexts in the evidence-policy ecosystem. It has potential applications in how academic-policy engagement interventions might be developed, evaluated, facilitated and improved, to ultimately support the use of evidence in decision-making.